Price incentives and consumer payment behaviour - Simon, John; Smith, Kylie; West, Tim (Journal of Banking & Finance, 2010)
In this paper we estimate the effect of particular price incentives on consumer payment patterns using transaction-level data. We find that participation in a loyalty program and access to an interest-free period tend to increase credit card use at the expense of alternative payment methods, such as debit cards and cash. Interestingly though, the pattern of substitution from cash and debit cards differs according to the price incentive. An implication of the findings is that the Reserve Bank reforms of the Australian payments system are likely to have influenced observed payment patterns.